The effect of overuse by primary healthcare institutions on medical expenses: an empirical study from the western regions of China - Zhang, Yao; Liu, Yingqi; Luo, Zhengxue; Zhou, Zhongliang; Gong, Shaoqing (Frontiers in Public Health, 2025)
BackgroundOveruse stands as an important factor in the unreasonable growth of healthcare expenditure in many countries, increasing the burden of both patients and national healthcare insurance. The heterogeneity of diseases results in significant differences in clinical manifestations and treatment sensitivity among different patients with the same illness, making it urgently necessary to explore and resolve the objective assessment and measurement of overuse. This study aims to investigate the current status of overuse in primary healthcare services in China, analyze and discuss the effect of overuse on medical expenses, and draw attention to the issue of overuse.MethodThe study adopted unannounced standardized patients to conduct 242 effective visits to 156 primary medical institutions in western Chinese province. The number of unnecessary medical service items reported after the visits is used to determine whether overuse exists. We set up a multiple linear regression model and used statistical methods to analyze the effect of different types of overuse on various medical expenses incurred by patients.Results(1) Among the 242 visits, overtreatment occurred 139 times, accounting for 57.44% of the total visits. Among them, over-examination accounted for 37.41%, and over-medication accounted for 62.58%. (2) Regarding medical expenditure, the average total medical cost per capita for the 242 valid visits was 32.73 yuan, with examination fees amounting to 22.96 yuan and drug costs totaling 13.60 yuan. (3) Compared to the non-overuse group, patients in the overuse group incurred a total cost of 106.57 yuan, which was 54.33 yuan higher. The examination fees for the overuse group were 69.74 yuan, representing an additional expenditure of 18.83 yuan compared to the non-overuse patients. Drug costs for the overuse group were 39.27 yuan, an increase of 35.74 yuan compared to the non-overuse patients. Thus, overuse led to an increase of 104, 27, and 91% in total medical costs, examination fees, and drug costs, respectively. (4) For every additional unnecessary medical service item, the total medical cost will increase by 18.66 yuan, the examination cost will increase by 3.65 yuan, and the drug cost will increase by 14.48 yuan, with an increase rate of 13, 17, and 20%, respectively. For every additional unnecessary medical examination, the examination cost will increase by 11.28 yuan, with an increase rate of 13%, while there is no significant impact on total medical costs and drug costs. For every additional unnecessary drug item, the total medical cost will increase by 19.71 yuan, and the drug cost will increase by 9.81 yuan, with an increase rate of 29 and 27%, respectively, while there is no significant impact on examination costs.ConclusionThe study found that overuse is highly prevalent in primary healthcare institutions in the western provinces of China, including two types: over-examination and over-medication, with the problem of excessive medication being more prominent. Overuse has led to an increase in medical expenses, which is specifically reflected in the rise of total medical costs and drug costs. The growth in the number of unnecessary medical items is the main cause of the unreasonable rise in medical expenses.